The association study of high-sensitivity C-reactive protein, pentraxin 3, nitrotyrosine, and insulin dose in patients with insulin-treated type 2 diabetes mellitus - Bala, Cornelia (Ther Clin Risk Manag, 2018)
PURPOSE: The objective of this study was to examine the association between insulin dose and high-sensitivity C-reactive protein (hsCRP), nitrotyrosine, and pentraxin 3 in patients with insulin-treated type 2 diabetes. PATIENTS AND METHODS: Eighty patients with type 2 diabetes treated with insulin for >6 months and with stable insulin doses (±10%) within 3 months before inclusion were enrolled in this study. Medical history, including use of insulin and insulin doses, concomitant diseases and medication, and anthropometric and routine biochemical parameters were collected for each patient. hsCRP, nitrotyrosine, and pentraxin 3 were measured in fasting conditions. Comparison analysis was performed according to the distribution in tertiles of insulin dose/kg of body weight, and linear regression adjusted for confounding factors was used to examine the associations between markers of inflammation, oxidative stress, and insulin dose. RESULTS: In the comparison analysis, no statistically significant difference was found between hsCRP, nitrotyrosine, and pentraxin 3 levels across tertiles of insulin dose expressed as IU/kg of body weight (p for trend >0.05 for all comparisons) except a significantly higher hsCRP level in tertile 3 compared to tertile 1 (3.9±3.6 vs 6.1±3.8 mg/dL, p=0.035). In regression analysis, after adjustment for age, gender, smoking, body mass index, glycated hemoglobin, C-peptide, metformin, antiplatelet, and statin use, only hsCRP levels were statistically significant associated with insulin dose/kg of body weight (β=0.237, p=0.043). CONCLUSION: In this sample of patients with type 2 diabetes treated with insulin for >6 months, hsCRP was positively associated with insulin doses. No such association was found for pentraxin 3, a more specific marker of vascular inflammation, and for nitrotyrosine as a marker of oxidative stress.